Comparison of the Effectiveness of Bonding Composite to Zirconia as a Repair Method - Celik, Gozde; Ismatullaev, Artur; Sari, Tugrul; Usumez, Aslihan (My University, 2016)
Chipping of the veneering porcelain is often reported in the literature. Intraoral repair of chipped veneering porcelain provides an option when the restoration cannot be removed and replaced. This in vitro study investigated the bond strength of two porcelain repair methods to the zirconia ceramic after different aging conditions. A total of 120 (Vita InCeram YZ) samples were divided into two main groups according to the different repair methods (n = 60). The first method was using a porcelain repair kit (Bisco), and the second method was repairing with a universal adhesive (Single Bond Universal Adhesive) and a composite resin (Z100). Each group was divided into two subgroups (n = 30) according to surface modification (with or without airborne particle abrasion). Each group was then divided into three subgroups (n = 10) depending on aging conditions. Shear bond strength tests were performed to measure the adhesion strength between composite and zirconia surfaces. Statistical analysis was performed with 3-way ANOVA, followed by Tukey HSD test ( = 0.05). Surface conditioning by airborne particle abrasion affected the strength values in the repair kit group compared with conventionally repaired group. Conventionally repaired group showed statistically significant higher bond strength values than repair kit group.